Contextualized Core English Glossary for nine-to-ten-year-old Ecuadorian Children. - Baquerizo Inca, Alexis Karina (2023)
This work is based on the results of Terminological and Documentary research about the cultural, religious and traditional aspects of the Ecuadorian people and territory. The objective of the present study is to provide language planners a set of terms that will enable the development of a curricular component through research of the different environments where the set population interacts. To achieve the latter, it was necessary to create a Contextualized Core English Glossary for nine-to-ten-year-old Ecuadorian Children that encompasses different aspects from the Ecuadorian culture, from roots to tradition, by using the EdiLIM educational software as a tool in the learning process of EFL for five graders.